Goldmining in Foreclosure Properties - Achenbach, George (New Jersey John Wiley and Sons, Inc., 2003)
Start Building Wealth Today by Investing in Distressed Properties!Combining proven strategies with nearly thirty years' experience in real estate, author George Achenbach takes you step by step through the entire foreclosure process-from the first notice of default to the foreclosure sale or auction to the final disposition of the property. Everything you need to know to purchase and profit from distress properties is here, including sample forms, worksheets, checklists, and real-life examples, as well as procedures to follow, evaluation techniques, and negotiating tips. There are even suggest.
Include Glossary, Appendix and Index
Keywords: Real estate investment -- Real property -- Foreclosure -- House buying